Pharmacokinetics and Tissue Distribution of Anwuligan in Rats after Intravenous and Intragastric Administration by Liquid Chromatography-Mass Spectrometry - Song, Yang (Molecules, 2019)
Anwuligan, a natural 2,3-dibenzylbutane lignan from the nutmeg mace of Myristica fragans, has been proved to possess a broad range of pharmacological effects. A rapid, simple, and sensitive liquid chromatography tandem mass spectrometry (LC-MS/MS) method has been established and successfully applied to the study of pharmacokinetics and tissue distribution of anwuligan after intravenous or intragastric administration. Sample preparation was carried out through a liquid-liquid extraction method with ethyl acetate as the extraction reagent. Arctigenin was used as the internal standard (IS). A gradient program was employed with a mobile phase consisting of 0.1% formic acid aqueous solution and acetonitrile. The mass spectrometer was operated in a positive ionization mode with multiple reaction monitoring. The transitions for quantification were m/z 329.0→205.0 for anwuligan and m/z 373.0→137.0 for IS, respectively. Calibration curves were linear over the ranges of 0.5–2000 ng/mL for both plasma samples and tissue samples (r > 0.996). The absolute bioavailability is 16.2%, which represented the existing of the obvious first-pass effect. An enterohepatic circulation was found after the intragastric administration. Anwuligan could be distributed rapidly and widely in different tissues and maintained a high concentration in the liver. The developed and validated LC-MS/MS method and the pharmacokinetic study of anwuligan would provide reference for the future investigation of the preclinical safety of anwuligan as a candidate drug.